2015
DOI: 10.1017/s000748531500036x
|View full text |Cite
|
Sign up to set email alerts
|

Pollinator communities in strawberry crops – variation at multiple spatial scales

Abstract: Predicting potential pollination services of wild bees in crops requires knowledge of their spatial distribution within fields. Field margins can serve as nesting and foraging habitats for wild bees and can be a source of pollinators. Regional differences in pollinator community composition may affect this spill-over of bees. We studied how regional and local differences affect the spatial distribution of wild bee species richness, activity-density and body size in crop fields. We sampled bees both from the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 63 publications
0
12
0
1
Order By: Relevance
“…Thus, functional composition in a community is determined by response traits (Ricotta and Moretti, 2011). For bees, the most important pollinator group (Klein et al, 2007), sociality, body size, nest location, nest behaviour and dietary specialization are the primary response traits used to explain community structure in agroecosystems (Rader et al, 2014;Ahrenfeldt et al, 2015;Warzecha et al, 2016), and some empirical studies have focused on mechanistic explanations to determine the influence of distinct environmental predictors on the diversity of these bees according to their response traits (Klein et al, 2003a;Le Feon et al, 2016). The evaluation of which response traits are more likely to explain the loss of species in scenarios, such as intensive farming regimes, can be an important step in promoting mitigation actions (Bartomeus et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, functional composition in a community is determined by response traits (Ricotta and Moretti, 2011). For bees, the most important pollinator group (Klein et al, 2007), sociality, body size, nest location, nest behaviour and dietary specialization are the primary response traits used to explain community structure in agroecosystems (Rader et al, 2014;Ahrenfeldt et al, 2015;Warzecha et al, 2016), and some empirical studies have focused on mechanistic explanations to determine the influence of distinct environmental predictors on the diversity of these bees according to their response traits (Klein et al, 2003a;Le Feon et al, 2016). The evaluation of which response traits are more likely to explain the loss of species in scenarios, such as intensive farming regimes, can be an important step in promoting mitigation actions (Bartomeus et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Strawberries require many individuals, species and bees of different sizes in order to develop optimally (Chagnon et al, 1989(Chagnon et al, , 1993Klatt et al, 2014). A previous study of pollinators in strawberry fields showed that wild bee species richness was lower in the field middle than closer to field margins (Ahrenfeldt et al, 2015). The current study found that wild bee activity-density and species richness changed during 40 days in spring and early summer which may have had a negative effect on pollination of cultivars flowering in early June and middle June when both…”
Section: Journal Of Melittologymentioning
confidence: 46%
“…Farmland represents 66% of the Danish landscape (Statistics Denmark, 2014) which means that in the intensely managed agricultural landscape of Denmark, farming systems and permanent field margins, and the resources they offer, may significantly influence the overall biodiversity. Bumble bee species and numbers have declined in Denmark (Dupont et al, 2011), but although 75% of wild and cultivated plant species require insect pollination (Holm, 1982;Prip et al, 1996), there is little knowledge about wild bees on agricultural land in this country (Ahrenfeldt et al, 2015;Calabuig, 2000;Henriksen & Langer, 2013). The current study helps fill this gap.…”
Section: Introductionmentioning
confidence: 92%
“…Dengan demikian, pemanfaatan serangga polinator liar bersama lebah piaraan diharapkan dapat meningkatkan hasil panen (Albano et al 2009b;Garibaldi et al 2013). Peningkatan kelimpahan dan pelestarian serangga polinator liar dapat dilakukan melalui penataan agroekosistem, di antaranya dengan menanam berbagai tumbuhan berbunga di sekitar pertanaman (Ahrenfeldt et al 2015;Sutter et al 2017;Ganser et al 2018). Anderson et al (2012) melaporkan proporsi buah dengan bentuk sempurna yang lebih banyak pada pertanaman stroberi organik dibandingkan pada pertanaman konvensional, yang diduga disebabkan oleh kelimpahan dan keanekaragaman serangga polinator yang lebih banyak pada kebun organik.…”
Section: Pembahasanunclassified